A survey of blow fly (Diptera: Calliphoridae) populations in Phoenix, Arizona - Meeds, Andrew W.; Rusch, Travis W.; Falcone, Danielle L.; Weidner, Lauren M. (Frontiers in Ecology and Evolution, 2023)
Utilizing insects in legal investigations as a tool for estimating forensically important timelines (e.g., minimum post-mortem interval (min-PMI)) is becoming more commonly used and accepted throughout the world. In the United States much of the climate is temperate, however, the Sonoran Desert is an arid location with extreme heat and irregular rainfall. Work on forensically relevant insects in this region is severely understudied. This study surveyed the populations of forensically important blow flies (Diptera: Calliphoridae) in Phoenix, Arizona for one year using traps baited with four different food sources. Nine species across four genera were collected with Lucilia sericata, Calliphora latifrons, and Lucilia mexicana accounting for 98.6% of total blow flies captured in the baited traps. Abundance drastically changed throughout the year, ranging from 500+ flies to 0 flies captured in a month, with species abundance correlating with temperature and humidity (e.g., Supplemental Figures 1-4). These results reveal that environmental conditions (i.e., maximum temperature and relative humidity) may limit blow fly activity or seasonally remove (or make inactive) entire local populations, thus affecting their ability to colonize remains and produce an accurate min-PMI.